2019
DOI: 10.1007/s10531-019-01803-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective spatial sampling designs for field surveys of species distribution

Abstract: High-quality biodiversity inventories are key tools to develop effective conservation strategies, but financial resources devoted to systematic species inventories are usually limited. Different sampling strategies have been proposed to efficiently allocate such limited resources (i.e. accessibility-based, stratified random and grid samplings), but their effectiveness may depend on the aim of the survey. Our aim was to assess which approach can provide the best trade-off between sampling costs and accuracy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
(63 reference statements)
0
17
1
Order By: Relevance
“…Monitoring of populations is an essential conservation task. Frequent monitoring is necessary to determine natural fluctuations, to detect declining trends, to ascertain the conservation status of populations and species and to ensure the effectiveness of eventual management measures [1][2][3][4]. This is recognised by the Habitats Directive of the European Union (Directive 92/43/EEC), which requires that member States regularly measure trends of populations of all listed species, to identify conservation priorities and to assess the efficiency of undertaken protection measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring of populations is an essential conservation task. Frequent monitoring is necessary to determine natural fluctuations, to detect declining trends, to ascertain the conservation status of populations and species and to ensure the effectiveness of eventual management measures [1][2][3][4]. This is recognised by the Habitats Directive of the European Union (Directive 92/43/EEC), which requires that member States regularly measure trends of populations of all listed species, to identify conservation priorities and to assess the efficiency of undertaken protection measures.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring programs are often limited by accessibility. Difficult access makes surveys more expensive and less feasible, thus the least accessible areas rarely are the focus of regular monitoring, and biodiversity surveys often remain concentrated in the most accessible areas [ 4 , 8 , 9 ]. Therefore, species living in inaccessible, remote areas often suffer insufficient monitoring, and declines or population changes might remain unnoticed.…”
Section: Introductionmentioning
confidence: 99%
“…Choosing the best spatial distribution of sampling effort is crucial should we want to optimize available resources. For instance, Marta et al (2019) found that when the aim is to gather information about species' ecology for conservation purposes, uniform sampling of the study area is preferable compared to stratified (habitat-specific) sampling. Similarly, in our study, we demonstrate that when the aim is to collect information about general patterns of species distributions, data-sharing is always preferable (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the choice of appropriate sampling design is crucial to make the best use of the available economic resources (Marta et al 2019). Additionally, collaboration among managers of neighbour protected areas may result in a better quality of the collected information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation